Qualitative Content Analysis of Moral Messages in the Film "Air Mata di Ujung Sajadah" - Fathoni, Fadhlan Dabith; Fitriananda An Nur (Jogjakarta Communication Conference (JCC), 2024)
Film is a mass communication that combines audio and visual aspects, serving to convey social and moral messages to the audience. Through storylines, dialogue, and compelling visualizations, films are able to  convey moral values and depictions of the reality of social life to their  audiences. Air Mata di Ujung Sajadah is an Indonesian religious drama  film released in 2023. This movie tells the story of a woman named Aini  who experiences various life trials, but remains firm in her stance and  always adheres to religious teachings. This study aims to analyze the  qualitative content of moral messages contained in the film Air Mata di  Ujung Sajadah. The method used in this research is descriptive qualitative  with content analysis techniques. The results showed that the movie Air  Mata di Ujung Sajadah contains strong moral messages about human relationships with God, self, and other humans, including nature. The  moral message is conveyed through various film elements, such as dialog,  character actions, and symbols contained in the film. This research is  expected to provide a deeper understanding of the moral values taught in  the movie Air Mata di Ujung Sajadah and contribute to the development  of science and culture.